Development Of The AI-312 Gas Turbine Engine For The Modernization Of The Ukrainian Gas Transport System With Import-Substituting Equipment - Kravchenko, Igor; Smirnov, Sergey; Kubatin, Valery (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
The article makes a generalized analysis of prospects of the European gas market and the condition of Ukraine’s gas transportation network as well as the struggle of Russia’s Gazprom to keep its position in the EU market. There is made the economic analysis of replacing gas turbine engines to gas-pumping units type GTK-10I. The article presents the advantages of employing the AI-312 gas-turbine engine in the gas transportation network of Ukraine, and considers the potential funding sources of the project. There is conducted the analysis of investment expenditures for development, and given proof of the social efficiency of the project.